An - Hales, Dianne (Wadsworth/Thomson Learning, 2001)
This new book from best-selling author Dianne Hales covers Fitness, Nutrition, Weight Control, and some selected Wellness topics. It emphasizes fitness as the best means to achieving the goal of feeling our best and living our lives to their fullest, and focuses on the key to living more happily and more healthfully: personal responsibility